The Lodge Maribaya Sebagai Salah Satu Pilihan Destinasi Ekowisata Kabupaten Bandung Barat - Susi Machdalena; Anggraeni Purnama Dewi; Ypsi Soeria Soemantri (Sekolah Vokasi, Universitas Gadjah Mada, 2018)
One of the eco-tourism destination in West Bandung Regency is ‘ The Lodge Maribaya’. It is a nature-based place, surroundings by the hills and pine-trees forest with full of the fresh-air. Besides the beautiful scenery, there are some children playground equipments, such as swings, and slides, there are also some play-equipments for adults, such as Sky–bike or Zip-bike, the equipment for riding the bike on a rope-track up in the sky. Then, a Sky wing is a swing in the edge of a cliff for selfie. The theory of Damanik and Weber (2006) is classified the tourism destination like this is a development of the natural resource to magically attraction , beautiful view, and comfortable fresh-air.